Assessing the Contribution of Marine Fisheries to the Indonesian Economy - Mardhani, Martahadi; Syardiansah, Syardiansah; Amilia, Suri; Aswadi, Khairul (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Marine fisheries significantly contribute to the economy of many regions and countries. This study aims to analyze the contribution of marine fisheries to economic growth in Indonesia. Johansen cointegration (JC) test and Fully Modified Ordinary Least Squares (FMOLS) are applied to investigate the contribution of the marine fisheries sector to economic growth. This study uses time series data from Statistics Indonesia (BPS) and the Ministry of Maritime Affairs and Fisheries (KKP) from 2010 to 2022. The findings indicated a long-term equilibrium among the measured variables. Marine fisheries have a significant and contributing effect on long-term economic development. The data demonstrate that the fisheries sector has become a source of food, job creation, and welfare for fishermen